PENGARUH LAYANAN INFORMASI TENTANG MANAJEMEN STRES TERHADAP RESILIENSI SISWA KELAS X IPA 1 SMA NEGERI 2 PEKANBARU T.A 2013/2014 - Rahmadeni Fitrah; Tri Umari; Sardi Yusuf (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2014)
Abstract: This research purposes to discover the reflection of student resilience before and after given the information services about the stress management and to determine the difference and influence of students resilience before and after given the information services about stress management. The population in this research involved all the students in class X IPA I, 32 students as sample by using total sampling technique. The research methodology adopted the quosi-experimental-one group pattern: pre-test and post-test design. The instrument of the research data collection used questionnaire. Based on the results of data processing shows that student resilience level before given the information services about stress management, is in low category (59,38%) while after given the information services about stress management is in medium category (62,5%). That means an increase in students resilience before and after given the infomation services about stress management. By using the “t” test with 62 dk and error standard is defined in the amount of 5% it can be seen that the value of t tally is bigger than t table (16,54%>1,980). It shows significant differences with students resilience enhancement before and after given the information services about stress management. From the results of correlational, r value=0,72. The coefficient determinant (r2) is 0,52. Which means the impact of the information services about stress management for students resilience level in class X IPA I SMA N 2 Pekanbaru shool yerar 2013/2014 are 52%.Keywords: Information Services, Stress Management, Resilience